Post-translational modifications in hepatocellular carcinoma: unlocking new frontiers in immunotherapy - Yuexian Piao; Naicui Zhai; Xiaoling Zhang; Xiaoling Zhang; Wenjie Zhao; Wenjie Zhao; Min Li (Frontiers in Immunology)
Liver cancer, particularly hepatocellular carcinoma (HCC), is one of the most common and aggressive malignancies worldwide. Immunotherapy has shown promising results in treating HCC, but its efficacy is often limited by complex mechanisms of immune evasion. Post-translational modifications (PTMs) of proteins play a critical role in regulating the immune responses within the tumor microenvironment (TME). These modifications influence protein function, stability, and interactions, which either promote or inhibit immune cell activity in cancer. In this mini-review, we explore the diverse PTMs that impact immune evasion in liver cancer, including glycosylation, phosphorylation, acetylation, and ubiquitination. We focus on how these PTMs regulate key immune checkpoint molecules such as PD-L1, CTLA-4, and the TCR complex. Furthermore, we discuss the potential of targeting PTMs in combination with existing immunotherapies to enhance the effectiveness of treatment in HCC. Understanding the role of PTMs in immune regulation may lead to the development of novel therapeutic strategies to overcome resistance to immunotherapy in liver cancer.